The Study of Sintering Process in Metal Forming - Setiawan, Agris; Pranoto, Aditya Wahyu; Adji Putrawan, Muhammad Rizki; Maharani, Monica (Journal of Metallurgical Engineering and Processing Technology, 2025)
Powder metallurgy is a technique used to produce metal components through the process of compacting and sintering metal powders. The sintering process involves heating the powder below its melting point, which allows the metal particles to bond together through a diffusion mechanism. This study examines the sintering mechanism, the factors that influence it, and the mechanical properties of the resulting materials. The research methods include a literature review and a literature study to collect information related to the sintering process of powder metal such as Al, Mg, Ti, Cu, Ni and Fe. The results show that sintering temperature and holding time of MMCs,AMCs have a significant effect on particle size that increase mechanical properties such as compressive strength, tensile strength, elastic modulus and density. Thus, a deeper understanding of the sintering process can improve the quality of metal products produced from powder metallurgy.